Genetic variation and conservation of one population of Crocodylus moreletii in captivity - Serna-Lagunes, Ricardo; Díaz-Rivera, Pablo (Instituto de Ecología, A.C., 2011)
Inbreeding is a frequent problem in isolated or captive populations, therefore it is necessary to implement strategies to minimize its incidence. Morelet´s crocodile, Crocodylus moreletii, is exploited in captivity and conservation of genetic variation is essential to its management and decision making in the release of offspring. The aim of this study was to analize population viability, extinctionrisk and effective population size of a C. moreletii captive population. We used simulation models and direct and ecological methods in order to obtain demographic and genetic measures appropriate for captive breeding practices of C. moreletii. It was found that it is feasible to establish a population of 200 crocodiles, which will ensure their survival for 50 years. Ne must be greater than 900, with a sex ratio of one male to 2.5 females and reproductive-adult size class. This would correspond to approximately 84% of effective reproductive crocodiles in the total population, having an inbreeding rate lower than 5.5%. This information would help to conserve 94% of the population genetic variation of C. moreletii in captivity for 100 years, and would let the transmission of viable genetic material to their offspring to be released to the environment.